Efficient uniform digital filter bank with linear phase and FRM technique for hearing aids - Parameshappa, G; Jayadevapp, D (International Journal of Engineering and Technology, 2018)
This paper attempts to present an uniform digital filter bank based on linear phase FIR and IIR filters applied for Frequency Response Masking (FRM) technique in hearing aid applications.In the proposed filter bank, nine uniformly spaced sub-bands are formed with the help of half band filters and masking filters. These nine channel FIR filter bank is realized using an interpolated half band linear phase FIR filter and an appropriate number of masking FIR filters. The nine channel IIR filter bank is realized using an interpolated half band approximately linear phase IIR filter and an appropriate number of masking filters. The proposed approximately linear phase IIR half band filter bank is compared with filter bank based on linear phase FIR half band filters in terms of area, power, memory and number of gates needed for implementation. The experiment was carried on various hearing loss cases and the results obtained from these tests proves that, the proposed filter bank achieved the required matching between audiograms and magnitude response of the filter bank at very reasonable range with less computational complexity.